The Effectiveness of Audio Visual - Based Learning Media to Improve German Writing Ability Class XII Students of Jakarta Lab Vocational School - Windy Aristin; Primardiana Hermilia Wijayati (Universitas Negeri Malang, 2022)
The purpose of this study was to determine the effectiveness of audio-visual media in improving the German writing skills of class XII students of SMK LAB Jakarta. The research method used is quantitative and ANCOVA analysis technique. The type of research used is quasi-experimental. The sample used in this study was 30 students of class XII A RPL as the experimental class and another class of XII B TKJ which amounted to 30 people as control class students who were chosen randomly (Random Sampling). The writing ability of students learning to use audio-visual media produces students who are able to develop creative ideas widely, able to increase accuracy in sentence structure or spelling in writing simple essays. The analysis successfully verified that the use of audio-visual media was effective in improving students' German writing skills. The statistical value of the ANCOVA test results yielded 0.004 < 0.05 and the F value was 8.813 < who receive treatment using audio-visual in the learning process have more diverse writing skills with broad ideas than students who apply conventional learning.